2013
DOI: 10.1007/s11103-013-0049-9
|View full text |Cite
|
Sign up to set email alerts
|

Plant species and organ influence the structure and subcellular localization of recombinant glycoproteins

Abstract: Many plant-based systems have been developed as bioreactors to produce recombinant proteins. The choice of system for large-scale production depends on its intrinsic expression efficiency and its propensity for scale-up, post-harvest storage and downstream processing. Factors that must be considered include the anticipated production scale, the value and intended use of the product, the geographical production area, the proximity of processing facilities, intellectual property, safety and economics. It is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 59 publications
0
22
1
Order By: Relevance
“…Accordingly, KDEL-tagged recombinant proteins are often found at least partially in PSVs, e.g., a single chain antibody fragment (scFv) in rice (Torres et al, 2001) and HSA in wheat (Arcalis et al, 2004). The direct ER-to-PSV transport of recombinant proteins has also been reported in dicot seeds (Petruccelli et al, 2006; Floss et al, 2009; Loos et al, 2011a; Morandini et al, 2011; Arcalis et al, 2013). The endogenous KDEL-tagged proteinase sulfhydryl-endopeptidase (SH-EP) behaves in a similar manner in the cotyledons of germinating mung bean seeds (Toyooka et al, 2000; Okamoto et al, 2003), and storage protein precursors in pumpkin seeds are delivered to PSVs in precursor-accumulating (PAC) vesicles (Hara-Nishimura et al, 1998).…”
Section: Storage Organelles and Endomembrane Traffic In Different Cermentioning
confidence: 74%
See 1 more Smart Citation
“…Accordingly, KDEL-tagged recombinant proteins are often found at least partially in PSVs, e.g., a single chain antibody fragment (scFv) in rice (Torres et al, 2001) and HSA in wheat (Arcalis et al, 2004). The direct ER-to-PSV transport of recombinant proteins has also been reported in dicot seeds (Petruccelli et al, 2006; Floss et al, 2009; Loos et al, 2011a; Morandini et al, 2011; Arcalis et al, 2013). The endogenous KDEL-tagged proteinase sulfhydryl-endopeptidase (SH-EP) behaves in a similar manner in the cotyledons of germinating mung bean seeds (Toyooka et al, 2000; Okamoto et al, 2003), and storage protein precursors in pumpkin seeds are delivered to PSVs in precursor-accumulating (PAC) vesicles (Hara-Nishimura et al, 1998).…”
Section: Storage Organelles and Endomembrane Traffic In Different Cermentioning
confidence: 74%
“…The lack of secretion in cereal endosperm often results in a distinct lack of typical apoplast N -glycan structures such as GnGnXF, which are abundant in proteins expressed in leaves (reviewed in Samyn-Petit et al, 2003; Arcalis et al, 2013). Glycoproteins that have not passed through the Golgi apparatus typically bear oligomannosidic structures (high-mannose glycans) whereas those in post-Golgi locations tend to bear complex, xylosylated and fucosylated N -glycans.…”
Section: Recombinant Protein Production In Cereal Endospermmentioning
confidence: 99%
“…The antibody 2G12 has been expressed in a wide range of plant-based platforms, including wild-type and glycoengineered systems, and has been targeted to different subcellular compartments, thus resulting in a huge variety of glycoforms. The detailed description of these data is beyond the scope of this paper, but overall it was found that the different glycan profiles do not affect the virus-neutralization activity of the antibody in vitro [72]. The impact of the different glycoforms in vivo should be considered in future studies, but it is likely that Fc-mediated antibody effector functions and antibody-dependent cell-mediated cytotoxicity could be influenced by different glycans and this should be considered in the context of systemic antibody administration [70].…”
Section: Discussionmentioning
confidence: 99%
“…This concept was developed in the EU project Pharma-Planta, which achieved the expression of 2G12 in several plant species and the fast-track development of transgenic tobacco as the primary production platform. The use of many different plants showed that the species, tissue, and subcellular compartment could affect the structure and composition of the antibody glycans, but this had no significant impact on the HIV-neutralization capacity of the antibody in vitro [72]. …”
Section: Monoclonal Antibody 2g12mentioning
confidence: 99%
“…3) (Arcalis et al 2013;Drakakaki et al 2006;Fanata et al 2013;Leonard et al 2002;Strasser et al 2007). First, b1,3-GalT produces the Galb1-3Glc-NAc structure by adding b1,3-galactose to non-reducing GlcNAc residues of GlcNAc (1,2) Man 3 XylFucGlcNAc 2 N-glycan (Leonard et al 2002).…”
Section: N-glycosylation In the Golgi Apparatus For Paucimannose-typementioning
confidence: 99%